Experiential Metafunction In Narrative Texts - Alemina Alemina; Nanang Panggabean (Journal of Language, Literature and Teaching, 2019)
This study was aimed at describing the types of process and the reason of using those types in two narrative texts. It was conducted by using descriptive qualitative design. The data were collected by using documetary technique. There were 170 clauses in the story of Sleeping Beauty which contained material process (120/70,5%),mental process (9/5,3%), relational process (17/10,5%), verbal process (8/4,7%), behavioral process (12/7,1%) and existential process (4/2,3%). In the story of Zeus, there were 112 clauses which contained material process (81/72%), mental process (3/2,7%), relational process (23/20,9%), verbal process (2/1,8%),behavioral process (2/1,8%) and existential process (1/0,9%). From the data, it was concluded that all the types of processes were found in both strories. The reason of using those types because there was some descriptions of the events and were dominated by the act of doing performed by the participants.